The Role of Green Finance in Sustainable Business Strategies: Opportunities and Challenges for Business Organizations - Lakasse, Syarifuddin; Amril, Amril; Syamsuri, Helmy; Jusman, Ikhsan Amar (CV Firmos, 2024)
Amidst increasing awareness of environmental and social issues, businesses worldwide are increasingly recognizing the importance of adopting sustainable business strategies. Green finance has become a popular approach among companies to integrate financial aspects with sustainable environmental goals. This research aims to investigate in-depth the opportunities and challenges associated with green finance practices for business organizations. The study is a literature review with a qualitative approach, utilizing descriptive analysis. Data for this research were obtained through a search of articles on Google Scholar spanning from 2014 to 2024. The study findings indicate that in an era where environmental awareness is on the rise, green finance practices are becoming increasingly crucial for companies looking to adopt sustainable business strategies. Green finance enables companies to integrate environmental values into investment decisions and fund allocation, creating incentives for more environmentally efficient business practices, and helping to mitigate environmental risks that may disrupt long-term operations. However, the implementation of green finance faces several challenges, including lack of understanding and awareness, complexity in measuring environmental impact, initial costs and economies of scale, limitations in data and measurement methods, as well as resource and internal capacity constraints. To address these challenges, cross-sector collaboration among private, government, and financial institutions is key.